2013
DOI: 10.1111/pcn.12125
|View full text |Cite
|
Sign up to set email alerts
|

Increased subsequent risk of acute coronary syndrome for patients with depressive disorder: A nationwide population‐based retrospective cohort study

Abstract: Aim:The purpose of this study was to explore the possible association between subsequent acute coronary syndrome (ACS) risk and depressive disorder. Methods:We used data from the National Health Insurance system of Taiwan to address the research topic. The exposure cohort contained 10 871 patients with new diagnoses of depressive disorders. Each patient was randomly frequency-matched for sex and age with four participants from the general population who did not have any ACS history before the index date (contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…Several studies have demonstrated the accuracy and validity of the diagnoses in the NHIRD. [14,21,22] Therefore, the NHIRD is a suitable tool for this study. This study was approved by the Institutional Review Board of Tri-Service General Hospital, Taiwan (approval number: 2-102-05-045).…”
Section: Methodsmentioning
confidence: 99%
“…Several studies have demonstrated the accuracy and validity of the diagnoses in the NHIRD. [14,21,22] Therefore, the NHIRD is a suitable tool for this study. This study was approved by the Institutional Review Board of Tri-Service General Hospital, Taiwan (approval number: 2-102-05-045).…”
Section: Methodsmentioning
confidence: 99%
“…The National Health Insurance (NHI) database of Taiwan is a reliable longitudinal population dataset, which has been used for various studies, including those on both asthma and depression (Lin et al 2014;Shen et al 2014Shen et al , 2015aLee et al 2015). The present study investigated whether major depressive disorder (MDD) is associated with incident asthma.…”
Section: Introductionmentioning
confidence: 99%
“…The National Health Insurance (NHI) database of Taiwan is a reliable longitudinal population dataset, which has been used for various studies, including those on both asthma and depression (Lin et al . 2014; Shen et al . 2014 , 2015 a ; Lee et al .…”
Section: Introductionmentioning
confidence: 99%